Mechanical stress triggers cardiomyocyte autophagy through angiotensin II type 1 receptor-mediated p38MAP kinase independently of angiotensin II. - Li Lin; Chuyi Tang; Jianfeng Xu; Yong Ye; Liqing Weng; Wei Wei; Junbo Ge; Xuebo Liu; Yunzeng Zou (PLoS ONE)
Angiotensin II (Ang II) type 1 (AT1) receptor is known to mediate a variety of physiological actions of Ang II including autophagy. However, the role of AT1 receptor in cardiomyocyte autophagy triggered by mechanical stress still remains elusive. The aim of this study was therefore to examine whether and how AT1 receptor participates in cardiomyocyte autophagy induced by mechanical stresses. A 48-hour mechanical stretch and a 4-week transverse aorta constriction (TAC) were imposed to cultured cardiomyocytes of neonatal rats and adult male C57B/L6 mice, respectively, to induce cardiomyocyte hypertrophy prior to the assessment of cardiomyocyte autophagy using LC3b-II. Losartan, an AT1 receptor blocker, but not PD123319, the AT2 inhibitor, was found to significantly reduce mechanical stretch-induced LC3b-II upregulation. Moreover, inhibition of p38MAP kinase attenuated not only mechanical stretch-induced cardiomyocyte hypertrophy but also autophagy. To the contrary, inhibition of ERK and JNK suppressed cardiac hypertrophy but not autophagy. Intriguingly, mechanical stretch-induced autophagy was significantly inhibited by Losartan in the absence of Ang II. Taken together, our results indicate that mechanical stress triggers cardiomyocyte autophagy through AT1 receptor-mediated activation of p38MAP kinase independently of Ang II.